The impact of the entrepreneurial marketing in the organization reputation - Saleh, Sami F.; Sadeq, Drman S.; Ansari, Manouchehr (Humanities Journal of University of Zakho, 2018)
The current study represents an attempt to find out the impact of the entrepreneurial marketing in the organization reputation, where the researchers prepared a theoretical framework beneficiaries from the theoretical literature of the subject and therefore, the current study seeks to answer the question (does the entrepreneurial marketing have an impact on the organization reputation?), and to answer it the default form was build which illustrates the nature of the relationship and impact to the study variables represented the entrepreneurial marketing and its dimensions (independent variable) and the organization reputation (dependent variable), thus, two main hypotheses with sub-assumptions have been formulated, the data was collected by a questionnaire distributed to the managers' and heads of departments in private hospitals in Dohuk city and analyzed through a set of statistical methods. The most important conclusions is a presence of a relationship and a significant impact between the entrepreneurial marketing dimensions and organization reputation. The main significant recommendations of the study are the local hospitals privacy in Duhok city need to adopt entrepreneurial marketing in their approaches, plans and work through focusing to customer and finding value to him, subsequently achieve the competitive advantage and build a good reputation distinguish itself from the competitors.